2016
DOI: 10.1039/c5ra18068f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a urea–formaldehyde resin adhesive on pyrolysis characteristics and volatiles emission of poplar particleboard

Abstract: To investigate the influence of urea–formaldehyde resin (UF resin) adhesive on the thermal utilization of wood waste, the pyrolysis of particleboard and its main components (poplar and UF resin) are studied in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…As the heating rate increases, the TG/DTG curves shift toward higher temperature (T), which could be attributed to the T gradient difference inside and outside the sample. Zhang et al [29] and Wang et al [30] found the same phenomenon. Additionally, affected by the mass transfer, the maximum mass loss rate from the DTG curve decreases and the hemicellulose shoulder gradually weakens or even disappears.…”
Section: Kinetic Analysismentioning
confidence: 58%
“…As the heating rate increases, the TG/DTG curves shift toward higher temperature (T), which could be attributed to the T gradient difference inside and outside the sample. Zhang et al [29] and Wang et al [30] found the same phenomenon. Additionally, affected by the mass transfer, the maximum mass loss rate from the DTG curve decreases and the hemicellulose shoulder gradually weakens or even disappears.…”
Section: Kinetic Analysismentioning
confidence: 58%
“…The pyrolysis liquids of wood-based panels contain a high content of nitric compounds, besides those Table 3. Main components of pyrolysis liquid of particleboard [1].…”
Section: Resultsmentioning
confidence: 99%
“…From GCMS analysis of the pyrolysis liquid of UF resin, it can be found that nitrogenous substances are the main components. Feng et al reported that the two most abundant components in pyrolysis liquids of UF resin are methyl-urea and N, N′-dimethyl-urea [17], while Zhang et al reported that the most relative content is N-ethylformamide [1]. In addition, other nitrogenous substances, such as 1-Methyl-2,4,5-trioxoimidazolidine, 2,3-Pyridinediamine, Pyrimidine,5-methyl-), urea, formyltrimethyl-, can also be detected in the pyrolysis liquid of UF resin.…”
Section: Liquidmentioning
confidence: 99%
See 2 more Smart Citations